Cryoballoon pulmonary vein isolation-mediated rise of sinus rate in patients with paroxysmal atrial fibrillation - Wagner, Lara; Darche, Fabrice Fernand; Thomas, Dierk; Lugenbiel, Patrick; Xynogalos, Panagiotis; Seide, Svenja; Scholz, Eberhard P.; Katus, Hugo; Schweizer, Patrick Alexander (Clinical research in cardiology, 2021)
Modulation of the cardiac autonomic nervous system by pulmonary vein isolation (PVI) influences the sinoatrial nodal rate. Little is known about the causes, maintenance and prognostic value of this phenomenon. We set out to explore the effects of cryoballoon PVI (cryo-PVI) on sinus rate and its significance for clinical outcome.